Factores de riesgo asociados a enfermedades crónico-degenerativas no transmisibles en adultos mayores del centro de salud Caluma Tipo C, periodo marzo – julio 2024 - Gutierrez Muñoz, Ana Maribel (2024)
The general objective of this study is to determine the modifiable risk factors associated with hypertension and diabetes to improve the lifestyles of senior adults treated at the Caluma Health Center during March and July 2024. The methodology applied consisted of a descriptive research, quantitative approach, and cross-sectional design, with a sample composed of 50 older adults of both sexes, the technique used was the survey. The results showed that older adults with hypertension and diabetes share varied socio-demographic characteristics, with an equal distribution by age and gender, mestizo ethnicity, and level of primary education completed. Both groups face multiple risk factors such as sedentary lifestyles (75%), with low levels of regular physical activity, especially aerobic exercise. Their dietary habits include frequent consumption of foods high in salt (76%), sugars (56%) and fats (68%). It was concluded that despite high adherence to treatment and medical visits, physical activity and diet still require significant improvements to optimize their overall health. KEYWORDS: MODIFIABLE RISK FACTORS, HYPERTENSION, DIABETES, SENIOR ADULTS, CALUMA HEALTH CENTER